Towards Clearer Jury Instructions - Gibbons, John (Language and Law / Linguagem e Direito, 2017)
In court cases involving juries, an important Forensic Linguistic issue is that the judge needs to communicate to jurors the law that applies to the case, and instruct them on the way they should view evidence and witnesses, the procedures they must use, confidentiality, etc. However, there is a second audience for these ’Jury Instructions’ - the Courts of Appeal. If the jury have not been correctly instructed, this can form the basis for an appeal. This second audience has led to complex Jury Instruction processes that may be poorly understood by jurors. To avoid miscarriages of justice, we need a Jury Instruction process that leads to maximal juror understanding. This paper discusses an attempt at revising instructions, by giving an example of instructions, showing the thinking that led to their revision, and the process and product of revision.